Erratum (Critical Studies in Television: The International Journal of Television Studies, 2018)
McElroy R, Nielsen JI and Noonan C (2018) Small is beautiful? The salience of scale and power to three European cultures of TV production. Critical Studies in Television 13(2): 169–187. DOI: 10.1177/1749602018763566. In this article, the following corrections apply to Table 1: ‘Overview of the broadcasters’ on page 171: The National Audience Share for S4C of 4.2% is referenced as BARB however this data is taken from correspondence with S4C directly. Note b should be attributed to the National Audience Share for S4C: 4.2%. The following correction applies to the first sentence of the first paragraph on page 176. This sentence should read: Therefore, a second source of data was gathered through exchanges at an Arts and Humanities Research Council (AHRC)-funded international network on ‘Television in Small Nations’ ( https://smallnationstv.org/ ), a collaborative project between the authors and industry partners including TG4, S4C and the European Broadcasting Union.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMTE3Ny8xNzQ5NjAyMDE4ODAzMTg4